The Pavilion of Trinidad & Tobago, and Grenada (Benjamin New Co., Ltd.)
The Pavilion of Trinidad & Tobago, and Grenada on the Ile Notre-Dame emphasizes the multi-racial and religious background of the three islands and the culture which has emerged from them.